Safety, acceptability and tolerability of uncoated and excipient-coated high density silicon micro-projection array patches in human subjects. Issue 48 (4th December 2017) - Griffin, Paul; Elliott, Suzanne; Krauer, Kenia; Davies, Cristyn; Rachel Skinner, S.; Anderson, Christopher D.; Forster, Angus
Highlights: The Nanopatch is a high-density array of micro-projections for vaccine delivery to the skin. The first clinical study with the Nanopatch has been performed. There were no unexpected adverse events. All applications resulted in erythema; the skin response was visible for several days or weeks. Applications were mostly pain-free; 15/18 subjects preferred the Nanopatch to needle and syringe. Abstract: Most vaccinations are performed by intramuscular injection with a needle and syringe. However, this method is not ideal due to limitations, such as the risk of needle-stick injury, the requirement for trained personnel to give injections and the need to reconstitute lyophilized vaccines. Therefore, we tested an alternative delivery technology that overcomes the problems with needle and syringe. The Nanopatch™ is an array of 10, 000 silicon micro-projections per cm 2 that can be dry-coated with vaccine for skin delivery. The high number and density of micro-projections means that high velocity application is required to achieve consistent skin penetration. Before clinically testing a vaccine Nanopatch, this study tests the safety, tolerability and acceptability/utility of uncoated and excipient-coated Nanopatches in healthy adults. Nanopatches were applied to skin of the upper arm and volar forearm and left in contact with the skin for two minutes before removal. The application sites were assessed for local skin response over 28 days. Acceptability interviews were also performed. No unexpected adverse events directly related to the Nanopatch application were reported. All applications of the Nanopatch resulted in an expected erythema response which faded between days 3 and 7. In some subjects, some skin discolouration was visible for several days or up to 3 weeks after application. The majority (83%) of subjects reported a preference for the Nanopatch compared to the needle and syringe and found the application process to be simple and acceptable. On a pain scale from 0 to 10, 78% of applications were scored "0" (no pain) with the average scores for less than 1. The results from this study demonstrate the feasibility of the Nanopatch to improve vaccination by showing that application of the product without vaccine to human skin is safe, tolerable and preferred to needle and syringe administration. Clinical trial registry ID: ACTRN1261500083549.